Design of Ultra-Wideband MIMO Antenna for Breast Tumor Detection. (14th November 2011) - Wang, Liting; Huang, Bin
Abstract : A MIMO antenna composed by microstrip line-fed circular slot antenna is proposed. This antenna is used in ultra-wideband microwave imaging systems aimed for early breast cancer detection. The antenna is designed to operate across the ultra-wideband frequency band in the air. The mutual coupling between the antenna elements has been investigated to be low enough for MIMO medical imaging applications. Both the simulation and measurement results are shown to illustrate the performances of the proposed antenna.